Influence of Structural Modification of Micro‐Porous Layer and Catalyst Layer on Performance and Water Management of PEM Fuel Cells: Hydrophobicity and Porosity. Issue 4 (23rd April 2020) - Mohseninia, A.; Kartouzian, D.; Eppler, M.; Langner, P.; Markötter, H.; Wilhelm, F.; Scholta, J.; Manke, I.
Abstract: The influence of hydrophobicity and porosity of the catalyst layer (CL) and cathode microporous layer (MPLC ) on water distribution and performance of polymer electrolyte membrane fuel cell (PEMFC) is investigated. Hydrophobicity of the layers is altered with the addition of PTFE (polytetrafluoroethylene) and mono‐dispersed polymer particles are utilized to introduce the macro‐pores with a diameter of 0.5 µm and 30 µm within the CL and MPLC, respectively. The treated materials are implemented in a specially designed fuel cell with an active area of 8 cm 2 to perform operando high‐resolution neutron tomography measurements. At high current density and humid operating conditions, MPLs with higher PTFE content increase the overall water content of the cell. The more hydrophobic MPL (40 wt.% PTFE) performs below the corresponding reference MPL (20 wt.% PTFE), whereas the performance result of double layer MPLC gives hint for further potential improvements of such design. The local water saturation beneath the land regions with the presence of perforated CL and MPLC is increased which is explained by lower capillary pressure barriers of bigger pores. Despite a higher water content, the perforated layers enhance the performance of the cell at both dry (RH 70%) and humid conditions (RH 120%), indicating that the parallel two‐phase flow is facilitated where the oxygen is transported through small pores and the water is preferentially transported through the bigger pores.